Tuesday

November 25, 2014

November 25, 2014

Posted by **BISWAJEET** on Tuesday, October 16, 2012 at 11:19am.

- MATH -
**Steve**, Tuesday, October 16, 2012 at 3:12pmThe F.T. says that if x-a is a factor of f(x), then p(a) = 0

So, if (5x+2) is a factor of f(x) = 3x^2+6x-4, then f(-2/5) = 0

f(-2/5) = -5.92

sure enough 3x^2+6x-4 / 5x+2 = 3x/5 + 24/25 remainder -148/25 = -5.92

**Answer this Question**

**Related Questions**

Calculus - a) prove that the function x^3 + 9x^2 +33x assumes the value -8 at ...

Algebra - I'm trying to solve x^3-3x^2-x+3 is less than zero. Except, I'm not ...

geometry - what is the diffwereence between a postulate and theorom

math - solve the equation x^3-5x^2-4x+20=0 I need a hint on how to solve this ...

Math - I want to know that if we have a set of data and we have to conclude if ...

Algebra - I'm trying to solve this Pythagorean Theorom problem. x^2+(2x^2)=32^2 ...

math - If the sides of a box all double in length, by how much does its volume ...

Algebra help - Solve Rational Inequalities x^2-x-2/x^2+5x+6<0 I cant figure ...

Algebra - I have several of these problems and am having trouble getting the ...

Math - Use the Factor Theorem to determine whether x-3 is a factor of P(x)=2x^3-...